ALTERATIONS IN THE STRUCTURE OF THE LIVER CELLIN CONGESTIVE HEART FAILURE - COSTERO, ISSAC CARLOS; BARROSO MOGUEL, R (INSTITUTO NACIONAL DE CARDIOLOGIA, CD. MEXICO, DF, MEX, 1947)
Summaries of other communications presented at the Second Inter-American Congress of Cardiology
AM HEART J
Keywords: ALTERATIONS, STRUCTURE, LIVER, CELLIN, CONGESTIVE, HEART, FAILURE; CIENCIAS MEDICAS; MEDICINA INTERNA; CARDIOLOGIA